PENGARUH PENGGUNAAN MEDIA REALIA TERHADAP HASIL BELAJAR PESERTA DIDIK MIN 40 ACEH BESAR - Wati Oviana; Najla Desna Fhasya; Misbahul Jannah (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh, 2023)
One of the factors causing low learning outcomes is the incompatibility of the media in delivering the material. Using media can make it easier for students to understand the material presented by the teacher, one of which is the use of Realia media. This study aims to analyze the effect of using Realia media on student learning outcomes in the material for changing the nature of objects in class V MIN 40 Aceh Besar. The research design used was Pre - Experimental Design type Intact Group Comparison. The population of this research is class V students totaling 28 people, using saturated sampling. Data was collected using tests and analyzed through statistical tests assisted by SPSS 20. The Independent Sample T-Test test results were obtained that tcount < ttable or -4.857 < 2.056. The results showed that there was a significant effect of using Realia media on student learning outcomes in the material for changing the nature of objects in class V MIN 40 Aceh Besar.Â